2012
DOI: 10.1038/pcan.2011.53
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits oxidative stress in human prostate carcinoma cells

Abstract: BACKGROUND: Emerging data suggest that obesity increases the risk of aggressive prostate cancer (PC), but the mechanisms underlying this relationship remain to be fully elucidated. Oxidative stress (OS) is a key process in the development and progression of PC. Adiponectin, an adipocyte-specific hormone, circulates at relatively high levels in healthy humans, but at reduced levels in obese subjects. Moreover, case-control studies also document lower levels of serum adiponectin in PC patients compared with heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
1
24
0
2
Order By: Relevance
“…Human ccRCC 786-O cells stably expressing shRNA specific to LKB1 (shLKB1) demonstrated a 47% knockdown of LKB1 protein expression compared with 786-O cells stably expressing noneffective scrambled control shRNA (shControl) (Figure 3A). Furthermore, when increasing concentrations of adiponectin, a known activator of AMPK (Lu et al , 2012), were used to treat cells, we demonstrate that the activation of AMPK was virtually abolished in shLKB1 cells when compared with shControl cells. The rate of proliferation was also significantly higher in shLKB1 cells than in shControl cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 89%
“…Human ccRCC 786-O cells stably expressing shRNA specific to LKB1 (shLKB1) demonstrated a 47% knockdown of LKB1 protein expression compared with 786-O cells stably expressing noneffective scrambled control shRNA (shControl) (Figure 3A). Furthermore, when increasing concentrations of adiponectin, a known activator of AMPK (Lu et al , 2012), were used to treat cells, we demonstrate that the activation of AMPK was virtually abolished in shLKB1 cells when compared with shControl cells. The rate of proliferation was also significantly higher in shLKB1 cells than in shControl cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 89%
“…In fact, it has been shown that the reduced concentrations of adiponectin observed in obesity may represent one of the mechanisms that connect obesity with the development and progression of cancer 83-86. importantly, adiponectin levels are decreased in obesity-associated insulin resistance and cancer 87. Insulin resistance is increased, with resultant elevation in insulin and bioavalible IGF1 levels, which enhance tumor cellular proliferation 88,89.…”
Section: Introductionmentioning
confidence: 99%
“…For example, adiponectin was used to treat damage resulting from alcoholic liver disease (Ouchi et al, 2011) and ethanol-induced gastric mucosal injury (Xu et al, 2003). In addition, adiponectin-mediated repair of periodontal damage (Yamamoto et al, 2012) and hearing loss has been demonstrated, and it plays important roles in prostate cancer (Salathia et al, 2013) and colon carcinoma (Lu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%